Manajemen Digital Sekolah Berbasis Google Workspace dalam Meningkatkan Kompetensi Guru dan Inovasi Pembelajaran (Studi Kasus SMP 57 Bandung) - Fifin Arifiani Agustiany; Hilmi Aulia Istiqomah; Ricky Yoseptry; Dini Indiriani; Rudi Setiawan; Syaripudin Syaripudin (STKIP PGRI SITUBONDO, 2025)
This study stems from the increasing demand for digital transformation in education, which calls for adaptive and technology-integrated school management. Google Workspace has emerged as a promising platform to enhance administrative efficiency and digital-based learning. The research aims to explore the implementation of digital school management based on Google Workspace to improve teacher competence and foster innovation in teaching practices. The study is grounded in the concepts of POAC (Planning, Organizing, Actuating, Controlling), TPACK (Technological Pedagogical Content Knowledge), and digital leadership, emphasizing the integration of technology in educational management. This case study was conducted at SMP Negeri 57 Bandung, located at Jl. Gempol Sari No. 142, RT 05/RW 09, Gempol Sari Village, Bandung Kulon District, Bandung City, West Java, Postal Code 40215. The results reveal that Google Workspace has been systematically implemented across four managerial stages and has positively impacted teachers' digital literacy, work efficiency, and creativity in designing technology-based learning. Innovative practices are reflected in collaborative learning, the use of interactive media, and active student engagement. The study recommends ongoing training and the development of data-driven evaluation systems to ensure the sustainable implementation of digital school management.